AN ANALYSIS OF INCLUSIVE SCHOOLS' EFFORTS TO PREVENT BULLYING - Nuriyanti, Risma; Nurhasanah, Mina; Romdon, Muhammad; Gumelar, Abih (Universitas Muhammadiyah Lamongan, 2024)
This research is motivated by the increasing number of bullying cases in Indonesia, especially in inclusive schools. The method used is a qualitative descriptive method with a phenomenology research type with data processing methods using interviews and observation. The results of this research show that BESTARI Utami elementary school, in an effort to prevent cases of bullying at school, is by carrying out intense communication with students so that students tell them anything that makes their students belittled, communication is also carried out by teachers with parents of students so that teachers are able to know about activities. what students do in the home environment and in the community environment and also teachers are able to know the students' personalities in environments other than the school environment. There are also other efforts such as taking notes when students want permission to leave the classroom during the learning process, then by reporting any incidents that are felt to violate norms in the school environment, both students to teachers and teachers to other teachers.